Social Changes and Factors Influencing Fishers’ Welfare in Kendari City - Saidin, Ainun Aviv; A Kinseng, Rilus; Indriana, Hana (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2022)
Indonesia, as a maritime country with rich marine resources can be used wisely for the welfare of the people; hence, there are various written and binding regulations in this regard. However, the wealth of marine resources in Kendari City does not guarantee the welfare of fishers. Fishers’ welfare is related to several factors and linked to social changes. Social change has an impact on various aspects of life. However, the impact of social change is not merely harmful, but it can also be beneficial to society. This study aims to analyze social changes and factors influencing fishers’ welfare in Kendari City. The writing method used is a quantitative approach through survey and qualitative approaches with in-depth interviews and literature studies. The results showed that there were horizontal and vertical social changes on fishers in Kendari City. The level of fishers’ welfare in Kendari City is categorized as moderate, and the factors related to the level of fishers’ welfare in Kendari City are fishing experience, the number of workers on board, the level of financial capital, the size of the ship, and the cost of fishing gear.